2013
DOI: 10.1017/s003329171300250x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in whole-brain functional connectivity observed in treatment-naive post-traumatic stress disorder patients following an earthquake

Abstract: PTSD patients showed abnormalities in whole-brain functional connectivity, primarily affecting the connectivities between the mPFC and limbic system, and connectivity between the PCC and insula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(106 citation statements)
references
References 41 publications
4
100
1
1
Order By: Relevance
“…Amygdala hyperactivity both at rest (Koch et al, 2016; Wang et al, 2016; Yan et al, 2013) and during negative emotion-inducing tasks (Etkin and Wager, 2007; Fonzo et al, 2010; Hayes et al, 2012; Patel et al, 2012; Pitman et al, 2012; Rauch et al, 2000; Shin et al, 2006; Simmons et al, 2011; St Jacques et al, 2011) has been consistently reported for PTSD. This hyperactivity suggests a failure of emotion regulation that could be instantiated by hypoconnectivity between the amygdala and the prefrontal emotion-regulation regions, including the ventromedial PFC (vmPFC) (Hayes et al, 2012; Patel et al, 2012) and medial prefrontal cortex (mPFC) (Jin et al, 2014). Brown et al (2014) also reported decreased resting-state functional connectivity between the right basolateral amygdala (BLA) complex and the left inferior frontal gyrus for PTSD compared to trauma-exposed controls.…”
Section: Discussionmentioning
confidence: 99%
“…Amygdala hyperactivity both at rest (Koch et al, 2016; Wang et al, 2016; Yan et al, 2013) and during negative emotion-inducing tasks (Etkin and Wager, 2007; Fonzo et al, 2010; Hayes et al, 2012; Patel et al, 2012; Pitman et al, 2012; Rauch et al, 2000; Shin et al, 2006; Simmons et al, 2011; St Jacques et al, 2011) has been consistently reported for PTSD. This hyperactivity suggests a failure of emotion regulation that could be instantiated by hypoconnectivity between the amygdala and the prefrontal emotion-regulation regions, including the ventromedial PFC (vmPFC) (Hayes et al, 2012; Patel et al, 2012) and medial prefrontal cortex (mPFC) (Jin et al, 2014). Brown et al (2014) also reported decreased resting-state functional connectivity between the right basolateral amygdala (BLA) complex and the left inferior frontal gyrus for PTSD compared to trauma-exposed controls.…”
Section: Discussionmentioning
confidence: 99%
“…Such changes in SN nodes are posited to underlie hyperarousal symptoms in patients with PTSD and overall dominance of the threat sensitivity circuit. 92 In addition, altered functional connectivity has been consistently noted between nodes of the DMN and SN, where increased connectivity has been reported between the ventral ACC (vACC; generally considered to be part of the mPFC) and PCC with the insula 94,97 ( Fig. 2).…”
Section: The Triple Network Model Of Psychopathology and Ptsdmentioning
confidence: 95%
“…The authors note that this finding may seem contradictory given previous work showing increased SN-DMN connectivity among individuals with PTSD (as described earlier), which is thought to underlie increased sensitivity to threat. 93,94,97,98 However, King and colleagues 35 suggested that given the role of the dACC in attentional and executive control, increased DMN-SN (dACC) connectivity may reflect an increased capacity for attentional shifting from internal selfreferential states to external stimuli, as is suggested in the case of increased DMN-CEN connectivity.…”
Section: Mindfulness and The Triple Network Model Of Psychopathologymentioning
confidence: 99%
“…Disturbances in resting-state functional connectivity between brain regions have been reported in several anxiety and mood disorders (4), and there have been increasing RS-fMRI reports conducted on PTSD (5,6). Baseline connectivity patterns have been investigated and abnormalities were observed in subcortical regions and default-mode network (7,8). While functional connectivity can reveal the coherence of remote brain regions in PTSD, less attention was paid to the abnormalities in coherence of local neural activity.…”
Section: Introductionmentioning
confidence: 99%